Identification of Leukotoxin and other vaccine candidate proteins in a Mannheimia haemolytica commercial antigen. Issue 9 (September 2016) - Tucci, Paula; Estevez, Verónica; Becco, Lorena; Cabrera-Cabrera, Florencia; Grotiuz, Germán; Reolon, Eduardo; Marín, Mónica
Abstract: Bovine Respiratory Disease is the most costly disease that affects beef and dairy cattle industry. Its etiology is multifactorial, arising from predisposing environmental stress conditions as well as the action of several different respiratory pathogens. This situation has hindered the development of effective control strategies. Although different type of vaccines are available, many currently marketed vaccines are based on inactivated cultures of the main viral and bacterial agents involved in this pathology. The molecular composition of commercial veterinary vaccines is a critical issue. The present work aims to define at the proteomic level the most relevant valence of a line of commercial respiratory vaccines widely used in Central and South America. Since Mannheimia haemolytica is responsible for most of the disease associated morbid-mortality, we focused on the main proteins secreted by this pathogen, in particular Leukotoxin A, its main virulence factor. By Western blot analysis and mass spectrometry, Leukotoxin A was identified as a major component of M. haemolytica culture supernatants. We also identified other ten M. haemolytica proteins, including outer membrane proteins, periplasmic transmembrane solute transporters and iron binding proteins, which are relevant to achieve protective immunity against the pathogen. This work allowed a detailed molecular characterization of this vaccine component, providing evidence of its quality and efficacy. Furthermore, our results contributed to the identification of several proteins of interest as subunit vaccine candidates.